2021
DOI: 10.1186/s12885-021-08674-y
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the transcriptional expression of minichromosome maintenance proteins as potential indicators of survival in patients with cervical cancer

Abstract: Background As major regulators of DNA replication in eukaryotes, minichromosome maintenance (MCM) proteins play an important role in the initiation and extension of DNA replication. MCMs and their related genes may be new markers of cell proliferation activity, which is of great significance for the diagnosis and prognosis of cervical cancer. Methods To explore the role of MCMs and their related genes in cervical cancer, various bioinformatics meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we reviewed 52 published articles associated with CC infections that provided transcriptome-guided hub proteins (genomic biomarkers) for cross-validation of the proposed key genes and the candidate drug agents. There were 255 hub genes reported in those 52 articles, with 7 hub proteins (AURKA, PCNA, CCNB1, CDC45, MCM2, TOP2A, CDK1) appearing in at least 5 articles ( Table S2 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 25 , 26 , 27 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Five (AURKA, CCNB1, MCM2, TOP2A, and CDK1) of the seven reported hub proteins were found to be similar to our suggested seven KGs.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that abnormal expression of MCM4 is associated with poor prognosis in patients with a variety of tumors (Liu et al, 2021;Wu and Xi, 2021). Xu et al (2021) found that patients with MCM4 high expression hepatocellular carcinoma had more advanced clinical stage and shorter survival time, and silencing MCM4 significantly inhibited the proliferation of hepatocellular carcinoma cells and the growth of hepatocellular carcinoma transplantation tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, SNRPE and MED13L had been reported as potential prognostic markers 70 , 71 . Furthermore, it has been indicated that CASC3, AGO3 and TARDBP could have a significant role in the prognosis of gastric cancer, hepatocellular carcinoma and cervical cancer respectively 72 74 .…”
Section: Discussionmentioning
confidence: 99%